Effect of carbonaceous impurities released from regenerated quartz tubes on the growth of ultra-long carbon nanotube forests. (15th October 2020) - Lee, Cheol-Hun; Park, Seongmin; Kim, Won Bae; Lee, Haemin; Lee, Sung-Hyun; Lee, Kun-Hong
Abstract: The yield and length of carbon nanotube (CNT) forests were increased by using regenerated quartz tubes. Carbonaceous impurities remained in the walls of the regenerated quartz tube. When CNT forests were synthesized in regenerated quartz tubes, the carbonaceous impurities were released at temperatures between 400 and 450 °C, and by facilitating nucleation, caused increase in the number density ( N Cat ) of Fe catalyst particles on the substrate. The substrate in the regenerated quartz tube had N Cat  = 6.0 × 10 10 /cm 2, whereas a fresh quartz tube had N Cat  = 7.7 × 10 9 /cm 2 . Furthermore, after the early stage (5 s) of synthesis process, the volumetric density of the CNT forest was higher in the regenerated quartz tube (0.016 g/cm 3 ) than in the fresh quartz tube (0.011 g/cm 3 ). When a regenerated quartz plate was placed in a fresh quartz tube, CNT forests were longer than when a fresh quartz tube was used alone. These results suggest that the carbonaceous impurity in the quartz tube establishes an environment that increases the reproducibility of synthesis of long CNT forests. Graphical abstract: Image 1